Acceleration of Communication Technology in Social and Cultural Change in Society - Zulkifli Amin; Syafaruddin Munthe (Lembaga Riset Mutiara Akbar, 2025)
This study aims to explore and deepen the use of information technology in education and social learning in schools and its impact on improving students' knowledge and motivation levels in social learning. A descriptive qualitative approach was used in this study with participants being teachers and high school students in Medan, North Sumatra, Indonesia. Research data were collected through interviews, observations, and documents. The findings of this study explain that the use of information technology such as online learning, the web, and social media in social learning provides an acceleration of socio-cultural change that has a positive impact on developing students' insights into broader learning materials, increasing students' knowledge of social materials and motivation in learning, which ultimately has an impact on social change in society. This study recommends that the use of information technology is very important in achieving learning objectives, developing knowledge and motivation. To achieve these goals, it is necessary to be supported by the ability and skills of teachers in utilizing technology in learning and the development of technological infrastructure in schools to support information technology-based social learning activities.